Myristylation of the large surface protein is required for hepatitis B virus in vitro infectivity - Bruss, Volker; Hagelstein, Jens; Gerhardt, Ellen; Galle, Peter R. (Virology, 1996)
The large surface protein (L) of the enveloped hepatitis B virus (HBV) is myristylated at glycine 2. To investigate whether this fatty acid moiety is required for HBV infectivity we made use of a point mutant in which the myristyl acceptor was mutated to a nonfunctional alanine. The mutant virus and a wild-type control were expressed in a human hepatoma cell line by transfection of genomic DNA constructs. Comparable amounts of virions were secreted by both strains as measured by the endogenous polymerase activity of immunoprecipitated virions. The presentation of an N-terminal epitope of L on the virion surface was not influenced by the mutation. To test the infectivity of this mutant virus primary human hepatocytes were incubated with the media of transfected cells. The covalently circular closed HBV DNA molecules generated after infection were discriminated from the open circular DNA genomes of inoculated virions by a sensitive PCR-based technique. The experiments demonstrated that the wild type was infectious but not the myristate negative mutant. This reflects the phenotype of an homologous duck hepatitis B virus mutant although the N-terminal L protein domains of this virus and of HBV show no primary sequence homology.
Elektronische Reproduktion der Druck-Ausgabe 25. Mai 2002
Gesehen am 06.03.2025